Quality Varies Across Health Insurance Marketplace Pricing Regions. Issue 7 (July 2015) - MacLean, Catherine H.; Marnoch, Eric; Sun, Zhao; Curtis, Jennifer; Burmeister, Jeff; Anum, Emmanuel A.; Belman, Michael; Nussbaum, Samuel R.
Abstract : Background: Although consumers purchasing health plans in the new Health Insurance Marketplace will be provided information on the cost and quality of participating health plans, it is unclear whether the state-wide plan quality averages that will be reported will accurately represent quality at the pricing region level where care will be received. Objectives: To evaluate whether currently reported state-wide health plan quality scores accurately represent quality within pricing regions established for the Health Insurance Marketplace. Research Design: Observational, historical cohort study using health plan administrative and pharmacy data. Subjects: A total of 5.2 million members enrolled in the preferred provider organization health plans of 1 large commercial California insurer in 2012. Measures: State-wide and pricing region performance on each of the 17 Healthcare Effectiveness Data and Information Set (HEDIS) measures. Results: Across the 17 measures assessed in each of the 19 pricing regions, scores were statistically different ( P <0.05) than the overall plan rate for 176 (54%). Variations in scores across regions were observed for each measure ranging from 6.4-percentage points for engagement in treatment for people with dependence of alcohol or other drugs to 47.2-percentage points for appropriate testing for pharyngitis among children. Conclusions: Quality scores in California vary greatly across geographic regions. Statewide averages may misrepresent the quality of care that consumers are likely to receive within a geographic area making difficult assessments about the value of the health care.